2012
DOI: 10.4236/ojvm.2012.21006
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Evaluation of an Oral Electrolyte Solution Formulated Based on Strong Ion Difference (SID) and Using Propionate as the Organic Anion in the Treatment of Neonatal Diarrheic Calves with Strong Ion Acidosis

Abstract: Background: It is postulated that the concentrations of the major strong ions (Na, K, and Cl) in oral electrolyte solutions play a major role in clinical efficacy of these solutions for rehydration and corrections of metabolic acid base derangements. Objectives: The purpose of this study was to test prospectively the efficacy of an OES (OES exp) formulated based on concentration of strong ion difference (SID) and propionate in a group of calves with naturally occurring neonatal diarrhea and clinically detectab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
13
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 8 publications
2
13
0
Order By: Relevance
“…A previous study (Sayers et al, 2016), investigating a predicted pH point at which a calf would be determined as clinically ill, suggested that a lower pH limit closer to 7.36 to be appropriate. This proposed value is in line with the value calculated from our study and with previously published normal values for a neonate calf (Stämpfli et al, 2012). However, it is recommended when the calf's sex, age, or breed type is known, that those ranges be used (Meyer and Harvey, 2004;Smith, 2009;Roland et al, 2014) to more precisely diagnose any possible health issues of a potentially ill calf.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…A previous study (Sayers et al, 2016), investigating a predicted pH point at which a calf would be determined as clinically ill, suggested that a lower pH limit closer to 7.36 to be appropriate. This proposed value is in line with the value calculated from our study and with previously published normal values for a neonate calf (Stämpfli et al, 2012). However, it is recommended when the calf's sex, age, or breed type is known, that those ranges be used (Meyer and Harvey, 2004;Smith, 2009;Roland et al, 2014) to more precisely diagnose any possible health issues of a potentially ill calf.…”
Section: Discussionsupporting
confidence: 87%
“…Adopting current blood gas reference ranges for healthy adult cattle (Divers and Peek, 2007;Stämpfli et al, 2012; to assess any blood gas derangements in neonates may be unwise, as differences exist between the ranges presented here and for adult bovines (Divers and Peek, 2007;Stämpfli et al, 2012;). This agrees with previous studies, which outlined similar findings regarding standard ranges for neonates (Rice, 1994;Gustin et al, 1997;Lorenz et al, 2005;Sayers et al, 2016).…”
Section: Discussionmentioning
confidence: 98%
“…Strong ions, both cations (positively charged) and anions (negatively charged), can be categorized as metabolizable or non-metabolizable in biological solutions at physiologic pH. The difference between the charge assigned to all non-metabolizable strong cations (usually sodium and potassium) and non-metabolizable strong anions (usually chloride) in an OES as fed is called the effective SID ( 111 ). The alkalinizing ability of an OES therefore reflects the concentration of strong anions such as acetate, propionate, citrate, that are metabolized to bicarbonate, formate that appears to be metabolized to carbon dioxide, and the concentration of the buffer ion bicarbonate, consequently the alkalinizing ability can be quantified by calculating the effective SID of the fed formulation ( 46 , 111 , 112 ).…”
Section: Oral Fluid Therapy In Neonatal Calves With Diarrheamentioning
confidence: 99%
“…Literature shows that ORS should be fed alongside regular milk provision, as withholding milk or feeding lower milk levels exacerbates weight loss, dehydration and prolongs recovery from diarrhoea (Garthwaite, Drackley, McCoy, & Jaster, 1994; Ollivett, Nydam, Linden, Bowman, & Van Amburgh, 2012). Other authors successfully tested hypertonic ORS (Na + > 130 mM) administered in between milk meals on diarrhoeic calves, but without including reference groups with lower tonicity ORS (Sayers, Kennedy, Krump, Sayers, & Kennedy, 2016; Stampfli, Oliver, & Pringle, 2012).…”
Section: Introductionmentioning
confidence: 99%